2014
DOI: 10.1111/maec.12238
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐related differences in size, function and regeneration of the major cheliped in the hermit crab Pagurus filholi

Abstract: Pagurus hermit crabs have a well‐developed right cheliped (major cheliped) and in some species the major cheliped of males is longer than that of females. This paper describes sex‐related differences in major cheliped length and regeneration pattern of the major cheliped in the hermit crab Pagurus filholi. We also examined the function of the major cheliped in male–male competition. Major cheliped length of males was longer than that of females in P. filholi. Males regenerated larger chelipeds than females at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
0
7
0
1
Order By: Relevance
“…P. middendorffii ; Yasuda & Wada, 2015) or in the reproductive season (e.g. P. filholi ; Matsuo et al ., 2015), and larger P. minutus males are more likely to win in male–male contests (Yasuda & Koga, 2016), as seen in other species (Wada et al ., 1999; Okamura & Goshima, 2010; Yasuda et al ., 2011; Tanikawa et al ., 2012), investing in growth for greater mating success might still affect male shell use in the reproductive season. This possibility is also supported by studies showing that some hermit crabs have a growth advantage in round-type shells over those in high-spired shells (e.g.…”
Section: Discussionmentioning
confidence: 86%
“…P. middendorffii ; Yasuda & Wada, 2015) or in the reproductive season (e.g. P. filholi ; Matsuo et al ., 2015), and larger P. minutus males are more likely to win in male–male contests (Yasuda & Koga, 2016), as seen in other species (Wada et al ., 1999; Okamura & Goshima, 2010; Yasuda et al ., 2011; Tanikawa et al ., 2012), investing in growth for greater mating success might still affect male shell use in the reproductive season. This possibility is also supported by studies showing that some hermit crabs have a growth advantage in round-type shells over those in high-spired shells (e.g.…”
Section: Discussionmentioning
confidence: 86%
“…Body size differences are one of the most common factors that determine the asymmetry of RHP between males in various taxa (Andersson 1994; Hardy and Briffa 2013), and the disadvantage created by loss of the major cheliped can be overcome by a (much) larger body size than that of an intact opponent (e.g., for the shore crab Carcinus maenas ; Abello et al 1994). As is the case in other animals, the advantage of larger body size for Pagurus species during male–male contests is well known (e.g., Wada et al 1999; Yoshino et al 2004; Suzuki et al 2012; Matsuo et al 2015a). In this study, we also demonstrated that both the giving-up decision and success of takeover in intruders were affected by body size relative to their opponents in P. minutus .…”
Section: Discussionmentioning
confidence: 92%
“…Male crayfish of form I are more likely to be dominant than those of form II because they possess a relatively larger chela (Guiasu and Dunham 1998). Matsuo et al (2015) examined the regeneration pattern of the major cheliped in both sexes of the hermit crab P. filholi during the reproductive season; males showed greater regeneration of the major cheliped than did fe-males, but males had reduced body size growth. Moreover, the male's investment in the major cheliped size can change, even over a single reproductive season.…”
Section: Discussionmentioning
confidence: 99%
“…Because the major cheliped is used as a weapon and helps the animal win contests-in which both sexes participate (Yoshino and Goshima 2002;Briffa and Dallaway 2007)-over gastropod shells (Neil 1985;Imafuku 1989), this trait is important regardless of sex. However, sexual size dimorphism of the major cheliped is common in this genus (e.g., P. nigrofascia,Y a s u d ae ta l .2011; P. filholi, Matsuo et al 2015;P. bernhardus, Briffa and Dallaway 2007;Doake et al 2010) as well as in other decapods.…”
Section: Introductionmentioning
confidence: 99%